Improving Patient Satisfaction Through Quality of Service for Diabetes Mellitus Wound Care Patients at Vera Cruz Community Health Center, Dili, Timor Leste - Felicidade do Rosario (Greenation Research & Yayasan Global Resarch National, 2026)
Diabetic wound care is a chronic health service that requires optimal service quality to ensure patient satisfaction. However, empirical studies on the relationship between service quality and patient satisfaction in the context of diabetic wound care in primary health care facilities in Timor Leste are still limited. This study aims to analyze the effect of service quality on patient satisfaction in diabetic wound care at the Vera Cruz Community Health Center in Dili, Timor Leste. This study used a quantitative approach with an explanatory design. The research instrument was adapted from the SERVQUAL model developed by Parasuraman. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the measurement and structural models. The results showed that service quality had a positive and significant effect on patient satisfaction. The resulting model met the validity and reliability criteria and had adequate explanatory power. These findings emphasize the importance of improving service quality, particularly in the aspects of reliability, responsiveness, and empathy, to increase patient satisfaction in chronic wound care services. This study contributes to enriching the literature on service quality and patient satisfaction in the context of primary health care in Timor Leste.